Analisis Kinerja Keuangan Koperasi Unit Desa (KUD) Koskopabo Tahun 2020 – 2024 - Nadia Oktavia; Awaluddin Awaluddin (Lembaga Yasin AlSys, 2026)
Cooperative financial performance is an important indicator in assessing the health level and business sustainability of cooperatives. Although financial performance analysis has been widely examined, studies that specifically analyze the financial performance of oil palm plantation-based Village Unit Cooperatives (KUD) using financial statement data over several periods remain relatively limited. This study aims to analyze the financial performance of KUD Koskopabo for the 2020–2024 period based on liquidity, solvency, and profitability ratios. This study used a quantitative approach with a descriptive design through a case study. The research object consisted of the financial statements of KUD Koskopabo for the 2020–2024 period, which were determined using saturated sampling (total sampling). Data were collected through documentation of statements of financial position and statements of remaining operating results, and were then analyzed using financial ratios based on Regulation of the Minister of State for Cooperatives and SMEs Number 06/Per/M.KUKM/V/2006. The results show that the financial performance of KUD Koskopabo is generally in fairly good condition. The cooperative has the ability to meet short-term obligations, maintain a relatively sound capital structure, and generate remaining operating results (SHU), although several financial indicators fluctuated during the study period. These findings contribute to the development of studies on cooperative financial statement analysis and expand understanding of the evaluation of cooperative health levels based on financial ratios. The conclusion of this study emphasizes the importance of effective management of assets, liabilities, and capital in maintaining cooperative business sustainability. The implications of this study can serve as evaluation material for cooperative administrators in improving the quality of financial management, while future research is recommended to expand the research object and use more comprehensive financial performance indicators.